Developing & Sustaining Innovative Organizations: Managing The Challenges - Khurana, Vijay Kumar; Gupta, Amit (Gyan Management Journal, 2013)
Modern era is an era of rapid and radical changes, which are continuously changing working of organizations and human beings across the world. These changes are bringing forth both opportunities and threats; accompanied by the constraint of very lesser time available to respond to such changes. These days, it is indeed survival of the fittest and fastest. To survive today, organizations are looking towards multiplicative levels of improvement and not fractional level of improvement. Words like Transformations, Disruptive Innovations etc have acquired increased significance. Piecemeal approach to innovation management cannot be fully helpful. As a result, there is emergence & growth of innovative organizations across the world, which churn out rapid & radical improvements and innovations continuously so that the business entity can survive on Jong-term basis and meet the expectations of all stakeholders. This paper examines the need for innovative organizations in the present era. The paper suggests the approaches to build an innovative organization. The paper explores the challenges likely to arise in the working and sustenance of innovative organizations and suggests ways to meet such challenges.